Between Ambition and Fiscal Reality: Strategic Environment, Budgeting, and Military Modernization in Indonesia (2020-2025) - Rienal Yaffid; Guntur Eko Saputro; Panji Suwarno (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2026)
This journal article analyses the trends in the strategic environment (lingstra) that underlie the formulation of Minimum Essential Force (MEF) stages I, II, and III, and evaluates the process of preparing Indonesia’s defence spending from 2020 to 2025. The analysis uses a qualitative approach and secondary data documentation from the Ministry of Defence, the Ministry of Finance, and the National Development Planning Agency. The article presents the dynamics of policies and the process of formulating the defence expenditure budget, including a comparison between the proposed and approved budgets. It also includes data on financing components from Pure Rupiah Funds, as well as domestic and foreign financing. The findings show that global and regional strategic environmental factors, such as geopolitical competition, military modernization in neighbouring countries, and advancements in defence technology, significantly influence Indonesia’s defence priorities.